Strategies of Driving Teachers in the Implementation of the New Paradigm Learning Process at SD Negeri 47 Palembang - Helen Saputri; Syarwani Ahmad; Nuril Furkan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
New Paradigm Learning is currently a challenge in itself for education in Indonesia. With Guru Penggerak which is one of the government's policies to respond to this challenge. Therefore, it is necessary to conduct research at SD Negeri 47 Palembang which currently have guru penggerak regarding the Strategy of the Guru Penggerak in the Implementation of the New Paradigm Learning Process which aims to describe and analyze the strategy of the Guru Penggerak in implementing the new paradigm learning process in terms of learning planning, learning implementation, assessment learning, inhibiting factors and efforts made to overcome obstacles in implementing the new paradigm learning process. This research was conducted at SD Negeri 47 Palembang with research methods using a qualitative research approach, while data collection techniques used interviews, observations and documents. The research data were analyzed using interactive model analysis techniques from Miles and Hubareman. Based on the research results, it was found that the planning and implementation of learning was carried out by Guru Penggerak at SD Negeri 47 Palembang regarding several new paradigm learning processes. Assessment of learning outcomes carried out cognitively and non-cognitively. The things that become obstacles include limited facilities and infrastructure, lack of teacher understanding, resistance to change, limited time and lack of support from parents.